ISOLATED GASTRIC TUBERCULOSIS MIMICKING MALIGNANCY - Memon, Wasim; Siddiqui, Saad (Journal of Ayub Medical College Abbottabad, 2016)
Isolated tuberculosis of upper gastrointestinal tract is a rare pathology, often mimicking malignancy in clinical presentation and radiological features. We present a case of middle aged gentleman with isolated tuberculosis of stomach, proven on histopathology and showing remarkable improvement on follow up. Keywords: Tuberculosis; Computed Tomography; Stomach; Gastric carcinoma